2003
DOI: 10.1080/13556210310001648176
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐related differences in alcohol and nicotine effects in C57BL/6J mice

Abstract: The present studies were aimed to identify possible age- and/or sex-related differences in the effects of alcohol and nicotine. Study 1 examined age-related differences in alcohol and nicotine effects. Adolescent and adult C57BL/6J male mice were injected with alcohol or nicotine. Results indicated that alcohol and nicotine induced hypothermia and reduced locomotor activity in both adolescent and adult mice. In both dependent variables, adults were more affected than adolescents that received the same alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 26 publications
9
27
2
Order By: Relevance
“…However, it does not correlate with the data from our acute studies in which adolescent and adult mice displayed no significant differences in three of four measures in responses to acute nicotine. In contrast, a previous study in C57BL /6J mice found that adults were more affected by nicotine in both hypothermia and locomotor activity tests (Lopez et al, 2003). Certainly, strain and dosing differences could contribute to this discrepancy.…”
Section: Adolescentcontrasting
confidence: 39%
“…However, it does not correlate with the data from our acute studies in which adolescent and adult mice displayed no significant differences in three of four measures in responses to acute nicotine. In contrast, a previous study in C57BL /6J mice found that adults were more affected by nicotine in both hypothermia and locomotor activity tests (Lopez et al, 2003). Certainly, strain and dosing differences could contribute to this discrepancy.…”
Section: Adolescentcontrasting
confidence: 39%
“…To examine sex differences following acute nicotine administration, we evaluated behaviors sensitive to acute exposure to nicotine, such as locomotor activity and antinociception. Previous studies ( Hatchell & Collins, 1980 ;Lopez et al, 2003 ) in mice of inbred strains show that females are less sensitive than males to nicotineinduced hypolocomotion, in agreement with our observations. In contrast, sex differences were not observed in mice of the ICR outbred strain ( Damaj, 2001 ).…”
Section: Discussionsupporting
confidence: 83%
“…Studies in mice also have observed sex differences. For example, female mice of different inbred strains are less sensitive than male mice to the depressant effects of nicotine on spontaneous motor activity ( Hatchell & Collins, 1980 ;Lopez, Simpson, White, & Randall, 2003 ), although no sex differences were observed between male and female mice of the outbred strain ICR ( Damaj, 2001 ). Differences in nicotine-induced antinociception also have been observed.…”
mentioning
confidence: 99%
“…Our observation that smoke exposure caused a dose-dependent further decrease in body temperature indicates that the inhalation of cigarette smoke decreases body temperature as such. This has previously been observed in rats (Altland et al, 1978) and is in accordance with observations on the hypothermic effects of inhalation of carbon monoxide and/or nicotine (Altland & Rattner, 1979;Lopez et al, 2003). In fact, inhalation of a wide range of xenobiotic substances such as ozone, acrylates, and formaldehyde (Watkinson et al, 2001;Jaeger & Gearhart, 1982;Silver et al, 1981) elicits a hypothermic response in rodents.…”
Section: Figsupporting
confidence: 74%